1999
DOI: 10.1126/science.286.5437.123
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole Rescue of a Cytosine Mutation in a Self-Cleaving Ribozyme

Abstract: Ribozymes use a number of the same catalytic strategies as protein enzymes. However, general base catalysis by a ribozyme has not been demonstrated. In the hepatitis delta virus antigenomic ribozyme, imidazole buffer rescued activity of a mutant with a cytosine-76 (C76) to uracil substitution. In addition, a C76 to adenine substitution reduced the apparent pKa (where Ka is the acid constant) of the self-cleavage reaction by an amount consistent with differences in the pKa values of these two side chains. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
281
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(306 citation statements)
references
References 26 publications
20
281
3
Order By: Relevance
“…Structural and mechanistic evidence indicates that the HDV ribozyme uses metal ion-bound water as the general base, and a cytosine nucleobase as a general acid (15,(64)(65)(66)(67). The TS ribozyme also appears to employ a hydrated metal ion as the general base, but at the present time we have not identified the general acid with confidence.…”
Section: The Hammerhead Ribozyme -The Role Of a 2'-hydroxyl Groupmentioning
confidence: 71%
“…Structural and mechanistic evidence indicates that the HDV ribozyme uses metal ion-bound water as the general base, and a cytosine nucleobase as a general acid (15,(64)(65)(66)(67). The TS ribozyme also appears to employ a hydrated metal ion as the general base, but at the present time we have not identified the general acid with confidence.…”
Section: The Hammerhead Ribozyme -The Role Of a 2'-hydroxyl Groupmentioning
confidence: 71%
“…2,65,80 The CPEB3 sequence also exhibits a flat pH profile around pH 7, as is observed in both HDV ribozymes under similar conditions. 2,45 Sequence-based searches using the human CPEB3 sequence revealed a remarkable conservation of this motif across mammalian CPEB3 genes (Fig. 4.5).…”
mentioning
confidence: 99%
“…Mutating the genomic C75 or antigenomic C76 residue to a U or G results in a loss of catalytic activity. 39,40,[44][45][46] The J4/2 strand is further stabilized by the A78 residue of the genomic ribozyme via an A-minor tertiary interaction with the C18 and G29 residues that form the middle base pair of the P3 helix. [34][35][36]47 A purine nucleotide is required 5 0 to A78 to allow for hydrogen bonding between its WatsonCrick face and the 2 0 OH of the C19 nucleotide at the base of P3.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 The inactive C75U mutation could be rescued with imidazole and the pK a of the reaction appeared to track with the pK a of nucleobases substituted at the key residue. 15,16 This suggested that C75 might function as a general acid to protonate the O5′ leaving group. However, subsequent crystal structures of the substrate form of the ribozyme showed that the C75 N3 is closer to the nucleophile, instead implicating C75 as a general base to deprotonate the 2′-OH.…”
Section: Hdv Ribozyme-nucleobase Catalysismentioning
confidence: 99%